2018
DOI: 10.3390/ijerph15102215
|View full text |Cite
|
Sign up to set email alerts
|

The Theory of Planned Behavior to Predict Protective Behavioral Intentions against PM2.5 in Parents of Young Children from Urban and Rural Beijing, China

Abstract: Smog and air pollution have fast become significant environmental problems and are attributed to rapid global industrialization and urbanization. Emissions of fine particulate matter with an aerodynamic diameter of ≤2.5 μm (PM2.5) increase smog and air pollution, with strong impacts on human health. Children are particularly vulnerable. While increasing studies are being conducted on the behaviors leading to PM2.5 toxicity from the perspective of environmental toxicants, there is a lack of research on factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 58 publications
1
22
0
Order By: Relevance
“…The questions were crafted based on a local brochure on air pollution designed by the Chinese Research Academy of Environmental Sciences and widely distributed to Beijing residents by the urban neighborhood offices, taking into account of feedback from a panel of local EPD officials and environmental scholars so as to ensure content validity. A similar approach has been used by Fryxell and Lo (2003) for constructing a scale of environmental knowledge and Liu et al (2018) for constructing measures of attitude, subjective norms, and environmental behaviors within a similar culture (i.e., Beijing and China). However, we did not use their scale because it measured the general environmental knowledge rather than specific environmental knowledge on air visibility; also in addition, their 40-item scale would be lengthy for our online survey.…”
Section: Methodsmentioning
confidence: 99%
“…The questions were crafted based on a local brochure on air pollution designed by the Chinese Research Academy of Environmental Sciences and widely distributed to Beijing residents by the urban neighborhood offices, taking into account of feedback from a panel of local EPD officials and environmental scholars so as to ensure content validity. A similar approach has been used by Fryxell and Lo (2003) for constructing a scale of environmental knowledge and Liu et al (2018) for constructing measures of attitude, subjective norms, and environmental behaviors within a similar culture (i.e., Beijing and China). However, we did not use their scale because it measured the general environmental knowledge rather than specific environmental knowledge on air visibility; also in addition, their 40-item scale would be lengthy for our online survey.…”
Section: Methodsmentioning
confidence: 99%
“…Behavioral Intention could be defined as a probability to engage in a certain behavior (Fishbein and Ajzen, 1975). According to TPB, behavioral intention shows how strong someone's intention to try and how much effort she or he is willing to do to perform the said behavior (Ajzen, 1991; Liu et al , 2018; Zeithaml et al , 1996). It can be concluded that the intention to follow the “Stay at Home” policy during the COVID-19 pandemic is a citizen's strong willingness to follow the policy.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…ItSAH is measured on three items adapted from Sumaedi et al (2020a, b). These items are developed by Zeithaml et al (1996), Peters and Templin (2010) and Liu et al (2018). The sample items of the scale are “I intend to stay at home during the COVID-19 pandemic” and “I urge other people to stay at home during COVID-19 pandemic.”…”
Section: Methodsmentioning
confidence: 99%
“…An intention is associated with behavioural, which shows a possibility to take part in a particular behaviour (Fishbein and Ajzen, 1975). It also underlines the individuals' willingness and extent of efforts which he/she made to accomplish behaviour (Ajzen, 1991; Zeithaml et al , 1996; Liu et al , 2018). In this way, an intention of individuals stay at home during the COVID-19 pandemic reflects the citizens' sturdy willing to act upon such the behaviour (Sumaedi et al , 2020a, b) which can be classified as a health-related behaviour.…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 96%